Russian collection of Brucella abortus vaccine strains: annotation, implementation and genomic analysis - Prasolova, Olga; Krylova, Ekaterina; Bogomazova, Alexandra; Soltynskaya, Irina; Sklyarov, Oleg; Gordeeva, Veronika; Timofeeva, Irina; Motorygin, Anton; Panin, Alexander (Frontiers in Veterinary Science, 2023)
Over the past 10 years, immunization of cattle in the Russia has been performed using vaccines from B. abortus strains 82, 19 and 75/79. To prevent brucellosis in small ruminants, two vaccines have been used, from the B. melitensis strain REV-1 and the B. abortus strain 19; note that twice as many animals have been immunized with the former vaccine than with the latter vaccine. The disadvantage of using these preparations is the formation of prolonged post-vaccination seropositivity, which is especially pronounced in animals after immunization with vaccines from B. abortus strain 19 and B. melitensis strain REV-1. This study aims to perform the whole genome sequencing of Brucella vaccine strains from the Russian collection. A bioinformatics analysis of the genomic data proved that the vaccine strains 75/79AB, 82, R-1096, and the KV 17/100 belong to ST-2, 104M to ST-1, KV 13/100 to ST-5. This analysis allowed us to characterize vaccine strains’s phylogenetic relationships and to prove the close relation of vaccine strains 75/79AB, 82, R-1096. Also, we defined candidate mutations in genes pmm, wbdA, wbkA, wboA, and eryB, which could be responsible for the attenuated virulence of vaccine strains. The complete genomic sequences of B. abortus strains make further studies of bacterial pathogenicity determinants and virulence phenotype feasible, as well as their use in quality control of animal medicines.